Proceedings of the Thirteenth ACM International Conference on Future Energy Systems 2022
DOI: 10.1145/3538637.3539615
|View full text |Cite
|
Sign up to set email alerts
|

Diversity for transfer in learning-based control of buildings

Abstract: The application of reinforcement learning to the optimal control of building systems has gained traction in recent years as it can cut the building energy consumption and improve human comfort. Despite using sample-efficient reinforcement learning algorithms, most related work requires several months of sensor data and operational parameters of the building to train an agent that outperforms existing rule-based controllers in a large multi-zone building. Moreover, exploring the large state and action spaces ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This study demonstrated that effective transfer occurs when the DRL agent is moved between buildings situated in similar climatic conditions, mainly when two out of the five layers of the neural network approximating the control policy in the source building were shared between source and target control agents. Zhang et al (2022a) introduced a strategy aimed at transferring a multi-agent RL from a source building with multiple zones to a target building. In this work, the authors developed a methodology to choose the most suitable pre-trained RL policy obtained from the source building prior to the transfer learning process, managing zone temperature setpoints in a Variable Air Volume (VAV) system.…”
Section: Related Work On Tl Applications For Reinforcement Learning C...mentioning
confidence: 99%
“…This study demonstrated that effective transfer occurs when the DRL agent is moved between buildings situated in similar climatic conditions, mainly when two out of the five layers of the neural network approximating the control policy in the source building were shared between source and target control agents. Zhang et al (2022a) introduced a strategy aimed at transferring a multi-agent RL from a source building with multiple zones to a target building. In this work, the authors developed a methodology to choose the most suitable pre-trained RL policy obtained from the source building prior to the transfer learning process, managing zone temperature setpoints in a Variable Air Volume (VAV) system.…”
Section: Related Work On Tl Applications For Reinforcement Learning C...mentioning
confidence: 99%
“…This study is the only one in which the use of heterogeneous TL was evaluated since it assessed the possibility of transferring a control policy between buildings with different numbers of thermal zones. Zhang et al [54] implemented a strategy to transfer a library of RL multi-agent control policies from a multi-zone source building to a target building. Before transferring the control policy, the authors designed a strategy to choose the best pre-trained RL policy among those obtained on the source building for the management of zone temperature setpoints in a Variable Air Volume (VAV) system.…”
Section: Related Work On Tl Applications For Advanced Controllers In ...mentioning
confidence: 99%
“…Similar to residential buildings, the concept of transfer learning has been explored recently and can be further expanded. Zhang et al reported that utilizing transfer learning for multi-agent DRL for multiple zone control of an HVAC system can reduce the energy consumption by 40.4% [83]. This improvement was observed even if the system policies originated in other buildings and were not locally retrained.…”
Section: Emphasizing Thermal Discomfort In the Office And Improving B...mentioning
confidence: 99%